Serum levels of TWEAK in patients with psoriasis vulgaris - Bilgiç, Özlem; Sivrikaya, Abdullah; Toker, Aysun; Ünlü, Ali; Altınyazar, Cevdet (Cytokine (Philadelphia, Pa.), 2016)
•Serum levels of TWEAK were significantly higher in psoriasis patients compared to controls.•Serum TWEAK levels showed a significant correlation with serum IL-23 levels.•Targeting TWEAK may be of therapeutic benefit in psoriasis. Tumour necrosis factor (TNF)-like weak inducer of apoptosis (TWEAK) has been implicated in the pathogenesis of a variety of inflammatory disorders and autoimmune diseases. However, studies conducted on the relationship of TWEAK and psoriasis patients are limited. In this study, we aimed to explore the serum levels of TWEAK and investigated whether TWEAK levels are associated with clinical variables and expression of other well-known psoriasis-related cytokines including IL-6, IL-23 and TNF-α. Forty-five patients with chronic plaque psoriasis and 43 controls were enrolled in this study. The severity of psoriasis was assessed by the Psoriasis Area and Severity Index (PASI). Serum levels of cytokines were measured using commercial enzyme-linked immunosorbent assay (ELISA) kits. The mean TWEAK, IL-6, IL-23, and TN-α levels were significantly higher in psoriasis patients than in control subjects. However, there were no significant correlations between the psoriasis severity, the illness duration and serum cytokine levels. This study shows that TWEAK may be associated with the pathogenesis of psoriasis, like TNF-α, IL-6, and IL-23.